Indonesian Teachers’ Perception on Duolingo for English Learning: Opportunities and Challenges - Putri Malika Alya; Farida Repelita Waty Br. Kembaren (Institut Agama Islam Negeri Palopo, 2025)
This study investigates Indonesian teachers’ perceptions of Duolingo as a supplementary tool for English instruction, focusing on its benefits, challenges, and feasibility in formal education. Using a qualitative case study at SMP Miftahul Husna, data were collected through interviews, observations, and document analysis. Findings indicate that while Duolingo enhances student engagement and autonomous learning through gamification, challenges persist regarding its limited emphasis on productive language skills, curriculum alignment, and technological accessibility. Teachers highlight the need for a blended learning approach that integrates Duolingo with structured classroom instruction to support communicative competence. This study offers insights into the role of digital platforms in Indonesian education and provides recommendations for their effective integration.